THE ROLE OF INSTITUTION INVOLVED IN THE PUBLIC FOREST RESOURCE MANAGEMENT AT KEMIRI VILLAGE, PANTI SUBDISTRICT - Diah Puspaningrum (UNEJ e-Proceeding, 2012)
This research was aimed to understand and analyze the role of institution that directly and indirectly involved in the Public Forest Resource Management at Kemiri Village, Panti Sub-district; Qualitative approach is used. Research type is case study. The purposively selected sample was then subjected to the snowball sampling. The data were collected by methods such as in depth interview (unstructured interview). Data sources are primary and secondary data. The word, sentences, or direct expressions from key informant were also obtained. The data analysis method is Miles and Huberman’s (1992) interactive model. The parties with direct participation in the PHBM (Pengelolaan Hutan Bersama Masyarakat) Program include Perhutani, LMDH Taman Putri, Lembaga Pemerintah Desa, and certain party with interest to forest preservation (stakeholder), such as Pesantren Al-Hasan. All these parties have role conjuncvitality.